1% Isoflurane and 1.2 μg/ml of Propofol: A Combination of Anesthetics That Causes the Least Damage to Hypoxic Neurons - Bu, Xinyue; Li, Tang; Guo, Di; Yang, Chenyi; Wang, Jinxin; Wang, Xinyi; Yang, Zhuo; Wang, Haiyun (Frontiers in Aging Neuroscience, 2020)
Backgrounds: Aging-related impairment of cerebral blood flow regulation leads to the disruption of neuronal micro-environmental homeostasis. Anesthetics should be carefully selected for aging patients since they have less cognition capacity. Effects and mechanisms of propofol or isoflurane have been widely investigated. However, how do different combinations of propofol and isoflurane affect neurons and the mechanism still need to be demonstrated. Methods: We cultured rat hippocampal neurons and established a hypoxic injury model to imitate the micro-environment of aging brains. Three different combinations of propofol and isoflurane were applied to find out an optimum group via CCK8 assay, LDH assay, Real-time qPCR and immunofluorescence of key proteins. Then BiP was silenced by siRNA to explore the mechanism of how isoflurane and propofol affect neurons. ER stress was measured by Western blot and immunofluorescence. To detect GABAAR α1 subunit proteostasis and its function, Real-time qPCR, immunoprecipitation and Western blot were carried out. Results: Hypoxic neurons showed no different changes on cell viability, LDH leakage and ER stress after treating with 1% isoflurane and 1.2 µg/ml propofol. Hypoxic neurons showed sharply increase of LDH leakage ER stress and decrease of cell viability after treating with 1.4% isoflurane and 0.6 µg/ml propofol or 0.5% isoflurane and 1.8 µg/ml propofol. After knockdown of BiP, the application of 1% isoflurane and 1.2 µg/ml propofol led to the decrease of GABAAR α1 subunit protein content and viability of cell, as well as aggravation of ER stress. Conclusion: A combination of 1% isoflurane and 1.2 µg/ml propofol causes the least damage compared to other dosages of both two drugs and endogenous BiP plays an important role in this process.